Equalizers or Enablers of Inequality? A Counterfactual Analysis of Racial and Residential Test Score Gaps in Year-Round and Nine-Month Schools. Issue 1 (November 2017) - Johnson, Odis; Wagner, Michael
Persistent racial/ethnic and residential disparities in test scores suggest schools fail to serve as society's great equalizers. Yet few studies have explored whether policies that adjust children's time in school are effective in reducing test-score inequality. We use ECLS-K data to compare children who attend year-round schools to those in nine-month schools, exploring (1) whether there were mean differences in the reading and math performance among first graders attending year-round and nine-month schools, (2) if racial and residential differences in children's test scores existed between the schooling types, and (3) if neighborhood effects related to academic performance strengthened or weakened as the children's exposure to schooling increased. Contrary to previous claims that schooling increases test-score inequality, we found no significant test-score differences among race-based groups of children according to neighborhood conditions in year-round schools. In contrast, we found prominent neighborhood effects and social class differences among children attending nine-month schools. We conclude with a discussion of the policy implications.